POSSIBILITIES OF LASER AND PHOTODYNAMIC THERAPY IN THE TREATMENT OF PURULENT-NECROTIC PROCESSES OF THE LOWER EXTREMITIES IN PATIENTS WITH DIABETES MELLITUS - Juraev G.G; Kasymov A.L; Musashaikhov X.T; Xojimetov D.Sh; Soliev M.B (Scholar Express Journals, 2023)
The article presents the results of clinical studies on the possibility of using laser and photodynamic therapy in the treatment of purulent-necrotic processes of the lower extremities in patients with diabetes mellitus. To this end, the authors conducted clinical studies of 110 patients operated in the department of purulent-septic surgery of the ASMI clinic. Studies have shown that after the opening of the purulent-necrotic process of the lower extremities in patients with diabetes mellitus with the use of laser therapy in combination with photosensitization, accelerated regression of inflammatory infiltration, complete cessation of purulent-necrotic discharge, wound cleansing and activation of regeneration processes
Keywords: Diabetic phlegmon; autopsy of the purulent-necrotic process